Literature Review: the Relationship Between Internal Control System of the Government (SPIP), Good Government Governance (GGG), and Fraud Prevention - Amsaroka, Muhamad Hayan; Yadiati, Winwin; Winarningsih, Srihadi (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2024)
The aim of this article is to clarify the connection between the government's internal control system, good government governance, and endeavors to thwart fraud, alongside the influencing factors. The methodology utilized encompasses a review of literature utilizing data drawn from international and national journals, with a total of 23 journals as the sample. From the analysis, it was determined that good government governance serves as an intermediary between the internal control system of government and the action of fraud prevention. In simpler terms, the more robust the internal control, the more adept it is at fostering effective and high-quality good governance, ultimately bolstering efforts to prevent fraud. Elements that must be taken into account for effective fraud prevention encompass: (1) Enhancing internal government supervision involves documenting and reinforcing the organization's dedication to the relevant code of ethics and conduct; (2) Ensuring a distinct division of roles and responsibilities; (3) Interpreting regulations comprehensively and ensuring consistent, unambiguous, and clear meanings; (4) It is essential to have qualified personnel matching their fields and expertise, whether through recruitment or competency development like education and training; (5) Utilizing information technology; (6) Conducting effective risk assessment and monitoring is crucial for overseeing organizational and identifying potential fraud risks.